1999
DOI: 10.3197/096327199129341888
|View full text |Cite
|
Sign up to set email alerts
|

Humans Valuing Nature: Synthesising Insights from Philosophy, Psychology and Economics

Abstract: A rational process for assessment of environmental policy options should be based on an appreciation of how humans value nature. Increased understanding of values will also contribute to the development of appropriate ways for us to relate to and manage natural areas. Over the past two decades, environmental philosophers have examined the notion that there is an intrinsic value in nature. Economists have attempted to define and measure the market and nonmarket economic values associated with decisions concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 56 publications
(5 reference statements)
1
116
0
10
Order By: Relevance
“…Landscape values are those that people attach to things such as ecosystem services, activities, and places (Brown 1984;Lockwood 1999). They reflect a person's perception of the landscape under valuation, their held values and associated preferences, and the context of the valuation.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape values are those that people attach to things such as ecosystem services, activities, and places (Brown 1984;Lockwood 1999). They reflect a person's perception of the landscape under valuation, their held values and associated preferences, and the context of the valuation.…”
Section: Introductionmentioning
confidence: 99%
“…While 'meaning' is difficult to measure since meanings are held individually and personally, designing interview questions or prompts that elicit responses from resource users to be expressive of meanings or sets of meanings can be developed. It has also been suggested that some sets of meanings are more common and have more knowledge and expressive power such that some classes of meanings may be easier to study than others (Lockwood 1999;McCool 2001). We hope that these methodological challenges encourage scholars to explore possible ways to resolve these difficulties, test the theoretical constructs proposed here and to present further cases to strengthen our understanding of how robustness is enhanced in social-ecological systems for improved benefit sharing.…”
Section: Discussionmentioning
confidence: 99%
“…Although a diversity of approaches is emerging, there is agreement that the manner in which users allocate value to resources and benefits is an important consideration when striving for equity, sustainability and efficiency in sharing benefits (Lockwood 1999;de Groot et al 2002;Boyd and Banzaf 2007;Wallace 2007;Fisher and Turner 2008). But these scholarly works have focussed predominantly on the expert classification of ecosystem services for the purpose of economic comparison.…”
Section: Perceptions Of Resource Value: Meanings Benefits and Behaviourmentioning
confidence: 99%
“…Une distinction utile est faite entre les « valeurs détenues » (held values), les principes et idées qui sont Vol. xLii, N os 2-3, 2012 Valeurs autochtones et modèles forestiers Le cas de la Première Nation des Innus d'Essipit 9 8 r e c h e r c h e s a m é r i n d i e n n e s a u Q u é b e c , x l i i , n o s 2 -3 , 2 0 1 2 importants pour les gens, et les « valeurs associées » (assigned values) à des objets, des endroits ou des institutions (Lockwood 1999). Dans un contexte autochtone, un exemple d'une « valeur détenue » pourrait être la connexion ou le lien réciproque avec la nature, alors qu'une « valeur associée » découlant de cela pourrait être l'importance du caribou, autant pour sa contribution à l'identité culturelle et au maintien des activités traditionnelles que pour la viande et la peau (Robinson et al 2012).…”
Section: Résumé De L'articleunclassified